Metal-Free Trifluoromethylthiolation of Alkyl Electrophiles via a Cascade of Thiocyanation and Nucleophilic Cyanide–CF3 Substitution - Matheis, Christian; Wang, Minyan; Krause, Thilo; Goossen, Lukas J. (Synlett, 2015)
A straightforward synthesis of alkyl trifluoromethyl thioethers was developed that starts from widely available alkyl halides or mesylates and the inexpensive reagents sodium thiocyanate and trimethyl(trifluoromethyl)silane. The alkyl electrophiles are converted in situ into the corresponding thiocyanates, which react with the nucleophilic Ruppert–Prakash reagent to give the corresponding trifluoromethyl thioethers via a Langlois-type CN–CF3 substitution. This process enables the efficient introduction of the pharmaceutically meaningful trifluoromethylthio groups into functionalized molecules without the need of metal catalysts or expensive preformed trifluoromethylthiolating agents.
Keywords: trifluoromethylthiolation; alkyl halides; fluorine; nucleophiles; sulfur